2019
DOI: 10.3390/ijerph16245117
|View full text |Cite
|
Sign up to set email alerts
|

Hand-Arm Vibration Assessment and Changes in the Thermal Map of the Skin in Tennis Athletes during the Service

Abstract: During recent years the number of tennis athletes has increased significantly. When playing tennis, the human body is exposed to many situations which can lead to human injuries, such as the so-called tennis elbow (lateral epicondylitis). In this work a biomechanical analysis of tennis athletes, particularly during the service, was performed, considering three different types of over-grip and the presence of one anti-vibrator device. One part of the study evaluates the exposure to hand-arm vibration of the ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Other works also conducted temperature analysis of upper limbs, like shoulder, arm, and forearm, presenting a temperature increase in the ROIs examined after the performance of an effort or labor [10,14,16,20,47,57]. The reduction in hand skin temperature that was found in this study might be due to the low level of repetitive effort present in lower risk tasks, where fewer technical actions occur at lower movement frequencies, as shown in Tables 3 and 4, and mainly, for the vasoconstrictor response of the skin that occurs in response to physical exercises [53,65]. Skin temperature reduction during exercise has been found by other studies [66], but especially in office tasks whose repetitive stress level is not high (such as typing and mouse use), there have been reductions in the temperature of the hand skin, as in the Gold et al [14] study.…”
Section: Discussionmentioning
confidence: 68%
“…Other works also conducted temperature analysis of upper limbs, like shoulder, arm, and forearm, presenting a temperature increase in the ROIs examined after the performance of an effort or labor [10,14,16,20,47,57]. The reduction in hand skin temperature that was found in this study might be due to the low level of repetitive effort present in lower risk tasks, where fewer technical actions occur at lower movement frequencies, as shown in Tables 3 and 4, and mainly, for the vasoconstrictor response of the skin that occurs in response to physical exercises [53,65]. Skin temperature reduction during exercise has been found by other studies [66], but especially in office tasks whose repetitive stress level is not high (such as typing and mouse use), there have been reductions in the temperature of the hand skin, as in the Gold et al [14] study.…”
Section: Discussionmentioning
confidence: 68%
“…Because it is inexpensive, non-invasive, and free of contraindication tools [3,4], in order to clarify the thermoregulatory processes and the physiological and metabolic responses to exercise, different studies have been carried out in many disciplines using infrared thermography [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Since it has been observed that cutaneous infrared radiation changes may be evidence acute physiological responses, thermography has been the subject of numerous studies in sport medicine, due to the possibility of obtaining immediate data about the functional state of the studied structures is a great advantage over other techniques. [1][2][3] Because it is inexpensive, non-invasive and free of contraindications tool, [4,5] in order to clarify the thermoregulatory processes and the physiological and metabolic responses to exercise, different studies have been carried out in many disciplines using infrared thermography [6][7][8].…”
Section: Introductionmentioning
confidence: 99%